Solutions for a troubled world - Macy, Mark (Boulder, Colo., USA : Earthview Press, 1987)
This books centres on peace as a possible if we can get in the habit of fostering such basic ingredients of peace as clear communication, equity and sensible regulation...in our personal lives, our social groups and our world
Index
Includes bibliographical references and index.
mf 22/10/2018
Loans
Keywords: Peace